The Building a Brand and Participation in Decreased Tackling Haze effects and Particulate matter Less Than 2.5 Micron (PM2.5) A Case Study: A Group of Students of Yupparaj Wittayalai School, Chiang Mai Province, Thailand - Suwattanarwong Phanphet; Sermkiat Jomjunyong; Ratanaree Suttipong; Saowaluk Reungsri; Athiwat Wangmai (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
The haze problem and particulate matter less than 2.5 microns (PM2.5) in Northern Thailand caused by climate change is directly impacted and indirectly impacted people. In the area is affected by the haze problem and particulate matter (PM2.5) the climate change is health effects of population, As reported by “Air Quality and Pollution City Ranking” on 12 March 2019 The world air-quality index in Chiang Mai province, as the ‘Rose of the North’ hit top of the scale as the worst polluted city in the world. The air quality index (AQI) hitting a staggering 271 with a diameter of fewer than 2.5 micrometers ranges from 170 micrograms per cubic meter (µg/m³) exceeding the safety standard of 50 µg/m³ or lower. The pollution is nasty in Chiang Mai, North Thailand, therefore it is necessary to create understanding and awareness of the haze problem and particulate matter in Chiang Mai province. This research is conducted by focusing on Mathayomsuksa 1 students include 40 people who are a group of students of Yupparaj Wittayalai School, Chiang Mai province, Thailand by exploring the understanding Organize activities to create awareness and participation in reducing the impact of the haze problem and particulate matter through the system “STEM EDUCATION”. The results of the activity evaluation made it known that students know the effects of haze problem and particulate matter with an average of 4.46 standard deviations equal to 0.59. As for the awareness and participation in reducing the impact of the haze problem and particulate matter through the STEM EDUCATION system, the average value is 3.5, the standard deviation is 0.72. In the overall picture, the mean is 4.18. The standard is 0.65. The level of satisfaction towards training on raising awareness of the haze problem and particulate matter is at a high level. Referring to my previous information, the researcher will develop tools and applications to create awareness and participation in reducing the impact of the haze problem and participate in matter for students in other schools.